Beat Machine: Embracing the Creative Limitations and Opportunities of Low-Cost Computers. - Brown, Andrew R.; Ferguson, John R. (Leonardo Music Journal, 2020)
The Beat Machine is a handheld music synthesizer and sequencer. The authors discuss the development of the Beat Machine and how creative constraints and opportunities were introduced by the particularities of low-cost microprocessors and associated electronics. The discussion is framed as an exemplar of Kåre Poulsgaard's concept of enactive individuation, a framework for relating material engagement to digital design and fabrication. In reflecting on the design and making of the Beat Machine the authors connect this framework with more established notions of creative interaction and the affordances of digital media.